Cigarette smoking and alcohol consumption are enemy of male fertility? A patho-radiological correlation study - Rai, Tina; Rai, Garjesh Singh (International Journal of Research in Medical Sciences, 2016)
Background: About 15% of the sexually active population is suffering from infertility in India, and in 50% of cases, male partner is involved, either as a primary cause or in combination a problem in the female partner. Modern life style changes like cigarette smoking and alcohol consumption are emerging out to cause a detrimental effect on male fertility due to adverse effects on semen volume, sperm morphology, total count and motility. The aim of this study was to study the effects of cigarette smoking and alcohol consumption on the semen parameters (volume, sperm motility, sperm count and morphology of sperms) and to study the morphological changes in testes in chronic alcoholics and/or cigarette smokers by high resolution sonography (HRSG). Methods: 200 male partners of infertile couple were included in the study referred from infertility clinic of department of obstetrics and gynecology in people’s college of medical sciences and research Centre, Bhopal, MP, India in-between Jan 2015 to December 2015. All the patients were divided in two group; each have 100 patients. Group A include 100 cases with history of smoking or alcohol consumption or both at least since 5yr. Group B also include 100 patients without any history of smoking and alcohol consumption or any medication for chronic illness and they will serve as controls. Detailed history about cigarette smoking and alcohol consumption was taken and recorded in the proforma. Semen sample has been collected in lab of department of pathology and results were recorded. All these patients were then subjected to HRSG of scrotum and testis in department of Radiodiagnosis of same institute to see any smoking or alcohol induced testicular atrophy. Results: Cigarette smoking has been found to have detrimental effects on male fertility particularly in moderate and heavy smokers who showed decreased semen volume, sperm count as well as sperm motility. Alcohol consumption resulted in abnormal sperm morphology. All the patients underwent for HRSG of scrotum and testis and 18% cases were found associated with testicular atrophy in group A and only 3% in group B. Conclusions: Heavy smoking and chronic alcohol consumption have detrimental effects on both quality as well as quantity of sperms. Moderate to heavy smoking was associated with decreased semen volume, sperm count and motility whereas chronic alcoholism was related to increased number of morphologically abnormal sperms and testicular atrophy.